Regulatory fit and evaluation mode : feeling right about hedonic and utilitarian consumption - Roy, Rajat (2008)
This research examines how regulatory focus affects the evaluation of hedonic and utilitarian attributes of products. My research found that promotion- focused people have higher evaluation of hedonic attributes over utilitarian attributes. The reverse was found for prevention focused subjects. In addition, the author found evidence that “evaluation mode” moderates the effect of regulatory fit on product evaluation. Specifically, I found that the above effect holds in a single mode of evaluation (SE) but not in a joint mode of evaluation (JE). In the joint mode of evaluation, subjects preferred the hedonic attributes irrespective of their regulatory focus conditions. The above pattern of results holds when product evaluation was used as the dependent variable. However, when purchase intention was used as the dependent variable, the fit effect was still found to hold under single evaluation mode. In the joint evaluation mode, a different kind of preference reversal was noticed. Both promotion and prevention focused subjects preferred the utilitarian over the hedonic attributes. The fit effect was then replicated for a different product category. In conformance with the extant literature, the research also found evidence that the fit effect takes place under condition of high involvement.